Особливості сімейств мікроконтролерів stm32 - Павлюк, С. Я. (ХНУРЕ, 2025)
Considered main families of microcontrollers STM32 from STMicroelectronics company and modern IDE from this company for programming these devices.
Keywords: мікроконтролер STM32; вбудована система; середовище розробки